2017
DOI: 10.1007/s11104-017-3545-x
|View full text |Cite
|
Sign up to set email alerts
|

Water soluble phosphate fertilizers for crops grown in calcareous soils – an outdated paradigm for recycled phosphorus fertilizers?

Abstract: Background and aimsThe current paradigm for phosphorus (P) fertilizers applied to calcareous soil is that almost entirely water soluble P fertilizers are efficient and sparingly soluble P fertilizers are not efficient P sources for crops. We hypothesize that this paradigm does not apply to recycled P fertilizers and that other P pools can explain the plant use of recycled P fertilizers on calcareous soil. Methods We applied 33 P isotopic dilution method to evaluate recycled P fertilizers based on plant P uptak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 73 publications
5
29
0
Order By: Relevance
“…As DGT is sampling diffusive P, these results suggest that the potential of a fertilizer to sustain the P nutrition of a crop is related to its ability to release P to the soil solution. Meyer et al (2017) confirmed this by showing that the amount of fertilizer P that was sequentially extractable by resin and NaHCO 3 predicted well the amount of P derived from recycling fertilizer taken up by ryegrass using the approach of Nanzer et al (2014a). Alt et al (2013) and Andersson et al (2016) used combined additions of cation and anion sinks to study the kinetics of P release from alkaline soils.…”
mentioning
confidence: 67%
“…As DGT is sampling diffusive P, these results suggest that the potential of a fertilizer to sustain the P nutrition of a crop is related to its ability to release P to the soil solution. Meyer et al (2017) confirmed this by showing that the amount of fertilizer P that was sequentially extractable by resin and NaHCO 3 predicted well the amount of P derived from recycling fertilizer taken up by ryegrass using the approach of Nanzer et al (2014a). Alt et al (2013) and Andersson et al (2016) used combined additions of cation and anion sinks to study the kinetics of P release from alkaline soils.…”
mentioning
confidence: 67%
“…12 Furthermore, calcium phosphate has also recently been shown to be an effective fertilizer when compared to conventional fertilizers and struvite. 16…”
Section: Introductionmentioning
confidence: 99%
“…The primary sources of phosphorus in the world are phosphate rocks, which are being depleted at a rapid rate due to increased demand as a result of population growth (Cordell et al, 2009). Wastewater mismanagement and the release of phosphorus into water bodies is the primary reason for environmental degradation such as eutrophication (Udert, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This process is also beneficial as it maximizes the recoverable nutrients from urine. It has been shown to be an effective method for producing calcium phosphate on-site, within novel nutrient recovery urinals (Flanagan and Randall, 2018), and the urine-derived fertilizers are just as effective as conventional fertilizers (Meyer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%